Desenvolvimento de sistemas para dispositivos móveis: Uma solução baseada em framework - Da Rocha, Alexander Haroldo [UNESP]; Correia, Ronaldo Celso Messias [UNESP]; Garcia, Rogério Eduardo [UNESP] (My University, 2009)
The technological evolution in wireless communications have motivated the development of systems for mobile equipments. However, such systems have not only constraints on environment execution, but also the need of synchronized data communication. And the data sets of systems running on computers (desktop or servers) have to be dealt by programs running on mobile equipments. The framework proposed in this paper, named PalmDataCollector, was developed to assist the incorporation of mobile modules to the existing desktop applications, reducing the time of development of mobile applications and eliminating the need to change systems already ready. The framework was developed using Java and SuperWaba tool, which has showed efficiency for Palm PDA device.
Development of systems for mobile devices: A framework-based solution